Multivariate realized stock market volatility - Gregory H. Bauer; Keith Vorking (Bank of Canada, 2007)
We present a new matrix-logarithm model of the realized covariance matrix of stock returns. The model uses latent factors which are functions of both lagged volatility and returns. The model has several advantages: it is parsimonious; it does not require imposing parameter restrictions; and, it results in a positive-definite covariance matrix. We apply the model to the covariance matrix of size-sorted stock returns and find that two factors are sufficient to capture most of the dynamics. We also introduce a new method to track an index using our model of the realized volatility covariance matrix.
Keywords: G14; C53; C32; 330; Econometric and statistical methods; Financial markets; Aktienmarkt; Kapitalertrag; Capital Asset Pricing Model